Research Progress on Aflatoxin Inhibitors and Their Mechanisms of Action - Shaowen WU; Weijie ZHOU; Siyuan YANG; Shijuan YAN (Guangdong nongye kexue)
Aflatoxins (AF) are secondary metabolites produced by fungi such as Aspergillus flavus, A. parasiticus, and other related species, possessing strong carcinogenic and toxic properties. Long-term exposure to low doses of aflatoxins can cause liver damage, immunosuppression, and growth retardation, while high-dose exposure can lead to acute poisoning or even death, seriously endangering the health of both humans and animals. Inhibiting aflatoxin biosynthesis at source is a crucial approach for controlling aflatoxin contamination, which has led to extensive research on aflatoxin inhibitors in recent years. This review systematically summarizes the research progress of different types of aflatoxin inhibitors over the past decade, primarily including three major categories: (1) Plant-derived inhibitors, encompassing essential oils, flavonoids, and polyphenolic compounds. (2) Microbial-derived inhibitors, covering lactic acid bacteria, Bacillus species, yeasts, and non-aflatoxigenic Aspergillus strains. (3) Chemically synthesized inhibitors, such as thiosemicarbazone compounds, organic acids and their derivatives, and antimicrobial peptides. Further analysis reveals that inhibitors function through five major mechanisms: (1) Disrupting cell membrane structural integrity and mitochondrial respiratory chain function in A. flavus, destroying fundamental cellular physiological structures. (2) Regulating the expression of key genes in the aflatoxin biosynthesis gene cluster and inhibiting activities of key enzymes such as polyketide synthase and monooxygenases, directly blocking aflatoxin biosynthetic pathway. (3) Modulating intracellular reactive oxygen species levels and antioxidant enzyme systems to maintain redox balance. (4) Inhibiting fungal development and differentiation processes, including key stages such as sclerotia formation, asexual reproduction, and spore germination. (5) Promoting detoxification of produced aflatoxins through physical adsorption, biodegradation, and chemical transformation. Based on mechanistic analysis, the review further explores potential targets for aflatoxin biosynthesis inhibition and provides perspectives on future directions for aflatoxin control strategies, aiming to provide theoretical guidance and a practical basis for developing effective control methods.